2014
DOI: 10.1111/bjh.13109
|View full text |Cite
|
Sign up to set email alerts
|

Switching to recombinant factor IX Fc fusion protein prophylaxis results in fewer infusions, decreased factor IX consumption and lower bleeding rates

Abstract: SummaryIn the phase 3 B-LONG [Recombinant Factor IX Fc Fusion Protein (rFIXFc) in Subjects with Haemophilia B] study, rFIXFc dosed every 1-2 weeks was safe and efficacious in previously treated subjects with haemophilia B. To date, there are no evaluations of transitioning from conventional to long-acting factor IX (FIX) prophylaxis. This post-hoc analysis of B-LONG subjects compared prophylaxis with other FIX products and rFIXFc. Pre-and on-study data were analysed to assess dosing regimen, weekly FIX consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 26 publications
(49 reference statements)
2
29
0
Order By: Relevance
“…Results from the non‐surgical arms of the multicentre phase 3 B‐LONG [Recombinant Factor IX Fc Fusion Protein (rFIXFc) in Subjects With Haemophilia B] study demonstrated a prolonged half‐life and lower consumption of recombinant FIX Fc fusion protein (rFIXFc), relative to rFIX, and the safety and efficacy of rFIXFc for treatment of bleeding and routine prophylaxis with dosing intervals of 1–2 weeks, which is longer than intervals seen with historical trials of rFIX (Powell et al , ; Powell et al , ). Here, we describe the surgical experience with rFIXFc in subjects with haemophilia B enrolled in B‐LONG.…”
mentioning
confidence: 99%
“…Results from the non‐surgical arms of the multicentre phase 3 B‐LONG [Recombinant Factor IX Fc Fusion Protein (rFIXFc) in Subjects With Haemophilia B] study demonstrated a prolonged half‐life and lower consumption of recombinant FIX Fc fusion protein (rFIXFc), relative to rFIX, and the safety and efficacy of rFIXFc for treatment of bleeding and routine prophylaxis with dosing intervals of 1–2 weeks, which is longer than intervals seen with historical trials of rFIX (Powell et al , ; Powell et al , ). Here, we describe the surgical experience with rFIXFc in subjects with haemophilia B enrolled in B‐LONG.…”
mentioning
confidence: 99%
“…In this study, individual PK profiles for rFIX were created for 5000 virtual patients by Monte Carlo simulation [12]. Monte Carlo simulation with the population pharmacokinetics of clotting factors is increasingly being used in hemophilia [13][14][15][16][17][18][19], although not extensively. Therefore, the principles of this technique are described below.…”
Section: Methodsmentioning
confidence: 99%
“…Posthoc analysis of the study demonstrated that prophylaxis with rFIXFc markedly reduced infusion frequency and FIX consumption; additionally, rFIXFc when administered weekly or every 10 days would maintain steady-state FIX activity greater than 1% in 95% and 89% of the patients, respectively. 52 Hemostatic response in 14 patients undergoing surgery was rated to be excellent (n ¼ 13) or good (n ¼ 1). 53 Interim analysis of the ongoing pediatric trial [NCT 014409046] reported the use of rFIXFc in 24 previously treated pediatric patients (age < 12 years) with HB (FIX activity 2 IU/dL).…”
Section: Extended Half-life Factor Concentratesmentioning
confidence: 99%